Balancing aesthetic and nature: a survey on landscape visual quality and ecosystem function among garden visitors - Mohamed, Noralizawati; Abdul Malek, Nurhayati; Mohamed Shaari, Shazwan (UiTM Press, 2025)
This study was conducted at 140 years of Penang Botanical Garden (PBG) which serves as a resource of ecosystem services and landscape visual aesthetics for visitors. This study has been undertaken to i) examine visitors’ perception on existing landscape visuals, ii) investigate visitor understanding on visual components and their function in garden’s ecosystem, iii) suggest guidelines and management strategies to balance between aesthetic and nature. The study employed structured questionnaire surveys from 330 visitors, and the instrument was adapted from Scenic Beauty Estimation Method introduced by Terry C. Daniel 1976. It is a quantitative measure of aesthetic preference for alternative wildland management system and prediction on the aesthetic consequences of alternative land uses. The data was analysed through descriptive statistical techniques. The analysis revealed that respondents highly preferred visual setting that combined with natural elements and produced sense of calm. They also have deep affection towards provisional services such as water, vegetation and air, but has limitation ability to understand the function of timber and soil towards garden’s ecosystem. It is suggested that the gap of understanding can be improved through information sharing and knowledge transfer by experts and PBG’s management through series of workshop, campaign, reading material and signage’s at the garden.